2003
DOI: 10.1212/01.wnl.0000094122.88929.0b
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil for myasthenia gravis

Abstract: The authors report a retrospective analysis of the use of mycophenolate mofetil (MyM) in 85 patients with autoimmune myasthenia gravis. The Myasthenia Gravis Foundation of America (MGFA) postintervention status (PIS) was used to characterize the treatment response in each patient. Sixty-two patients (73%) achieved a PIS status indicating improvement. Quantitative strength testing performed on the majority of patients before and after treatment also improved. Side effects to MyM were observed in 27% of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(100 citation statements)
references
References 10 publications
1
97
0
2
Order By: Relevance
“…Patient data fully support these findings as improvements in functional status, manual muscle testing and jitter in single fiber EMG were reported after MMF treatment in MG (Chaudhry et al, 2001;Ciafaloni et al, 2001;Hampton, 2007;Meriggioli et al, 2003a;Meriggioli et al, 2003b;Mowzoon et al, 2001;Prakash et al, 2007). Interestingly, the anti-rat AChR antibody titers observed in the present study were moreover exponentially correlated with curare resistance of neuromuscular transmission.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Patient data fully support these findings as improvements in functional status, manual muscle testing and jitter in single fiber EMG were reported after MMF treatment in MG (Chaudhry et al, 2001;Ciafaloni et al, 2001;Hampton, 2007;Meriggioli et al, 2003a;Meriggioli et al, 2003b;Mowzoon et al, 2001;Prakash et al, 2007). Interestingly, the anti-rat AChR antibody titers observed in the present study were moreover exponentially correlated with curare resistance of neuromuscular transmission.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, MMF seemed to be highly efficient in preventing clinical MG symptoms in 95% of immunized animals. Single case reports and several small clinical studies concerning MMF treatment in MG confirm the abovementioned observations as most patients were able to reach pharmacological remission, and improved manual muscle testing and quantitative MG score after several months of treatment (Caponnetto et al, 2001;Chaudhry et al, 2001;Ciafaloni et al, 2001;Hauser et al, 1998;Lim et al, 2007;Meriggioli et al, 2003a;Meriggioli et al, 2003b;Mowzoon et al, 2001;Prakash et al, 2007;Schneider et al, 2001). In contrast, two recently completed large phase 3 prospective, multicenter, placebo-controlled trials showed little or no effect of MMF when it was used as an adjunctive treatment to corticosteroids.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This results in inhibition of purine synthesis selectively in lymphocytes, thereby inhibiting their proliferation (Allison, Kowalski et al 1993). In a larger retrospective study, MyM was associated with clinical improvement in approximately 70% of patients after a period of approximately 11 weeks (Meriggioli, Ciafaloni et al 2003). MyM is also well tolerated in most patients and only discontinued due to the adverse effects in a very small fraction of patients, the most common reason being gastrointestinal intolerance, such as diarrhea.…”
Section: T-cell Inhibiting Medicationsmentioning
confidence: 99%
“…In addition to anticholinesterase drugs, most patients with generalised MG require long-term treatment with steroids and immunosuppressive drugs, of which the most commonly used include azathioprine, mycophenolate mofetil and ciclosporin. [2][3][4][5] Between 5 and 10% of patients remain refractory to such treatment. 2,6 Other immunosuppressive drugs may then be considered, including cyclophosphamide, 7 tacrolimus 8 and etanercept, 9 whose efficiency has not been assessed on the basis of double-blind clinical trials.…”
mentioning
confidence: 99%